Optimalization of GA3 Concentration and Soaking Time to Increase Seed Germination of Phyllanthus niruri L. - Seftiani, Shalma; Sujarwati, Sujarwati (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2020)
Phyllanthus niruri L. is a medicinal plant that has been developed as phytopharmaca. The efforts to cultivate P. niruri need to be done to fulfil the large-scale and sustainable needs as raw material for traditional medicine. Propagation of P. niruri using seeds is still a problem, because the seeds have low seed germination. One of the plant hormones that play an important role in germination is gibberellins (GA3). This study aimed to determine the effect of concentration of GA3, soaking time, and the interaction of both factors on P.niruri seed germination, and determine the optimal concentration of GA3 and soaking time to increase germination of P.niruri seeds. It was arranged in a factorial completely randomized design with two factors. The first factor was the concentration of GA3 i.e 0, 300, 310, 320, 330, 340, 350, 360 ppm. The second factor was the soaking time i.e 6, 12, 18, and 24 hours. The parameters observed were the percentage of germination, germination time, and vigour index. Data were analyzed using ANOVA and DMRT (α = 0,05). The result showed that the interaction between GA3 concentration and soaking time had significantly affected the percentage of germination and vigour index. Soaking seeds in GA3 concentration of 360 ppm for 18 hours is the optimal treatment that produces a percentage of germination was 83.33%, germination time was 3.38 days, and vigour index was 2.74 seeds/day